Blocked at the Stomatal Gate, a Key Step of Wheat Stb16q-Mediated Resistance to Zymoseptoria tritici - Battache, Mélissa; Lebrun, Marc-Henri; Sakai, Kaori; Soudière, Olivier; Cambon, Florence; Langin, Thierry; Saintenac, Cyrille (Frontiers in Plant Science, 2022)
Septoria tritici blotch (STB), caused by the fungus Zymoseptoria tritici, is among the most threatening wheat diseases in Europe. Genetic resistance remains one of the main environmentally sustainable strategies to efficiently control STB. However, the molecular and physiological mechanisms underlying resistance are still unknown, limiting the implementation of knowledge-driven management strategies. Among the 22 known major resistance genes (Stb), the recently cloned Stb16q gene encodes a cysteine-rich receptor-like kinase conferring a full broad-spectrum resistance against Z. tritici. Here, we showed that an avirulent Z. tritici inoculated on Stb16q quasi near isogenic lines (NILs) either by infiltration into leaf tissues or by brush inoculation of wounded tissues partially bypasses Stb16q-mediated resistance. To understand this bypass, we monitored the infection of GFP-labeled avirulent and virulent isolates on Stb16q NILs, from germination to pycnidia formation. This quantitative cytological analysis revealed that 95% of the penetration attempts were unsuccessful in the Stb16q incompatible interaction, while almost all succeeded in compatible interactions. Infectious hyphae resulting from the few successful penetration events in the Stb16q incompatible interaction were arrested in the sub-stomatal cavity of the primary-infected stomata. These results indicate that Stb16q-mediated resistance mainly blocks the avirulent isolate during its stomatal penetration into wheat tissue. Analyses of stomatal aperture of the Stb16q NILs during infection revealed that Stb16q triggers a temporary stomatal closure in response to an avirulent isolate. Finally, we showed that infiltrating avirulent isolates into leaves of the Stb6 and Stb9 NILs also partially bypasses resistances, suggesting that arrest during stomatal penetration might be a common major mechanism for Stb-mediated resistances.